Born of war in Colombia: reproductive violence and memories of absence - Sanchez Parra, Tatiana (Rutgers University Press, 2023)
Born of War in Colombia addresses why people born of conflict-related sexual violence remain unseen within transitional justice agendas. In Colombia, there are generations of children born of conflict-related sexual violence across the country. Whispers of their presence have traveled outside their communities. They also exist within the country s domestic reparations program, which entitles them to reparations. Drawing on an immersive feminist ethnography with a community that endured a paramilitary confinement, the book reveals how a past-oriented and harm-centered model of transitional justice has converged with a restricted notion of gendered victimhood and the patriarchal politics of reproduction to render the bodies and experiences of people born of conflict-related sexual violence unintelligible to those seeking to understand and address the consequences of war in Colombia